Effects of iopromide contrast agents on kidney iNOS expression and tubular histopathology alterations - Pranoto, Indrianto W.; Djojodimejo, Tarmono; Soebadi , Mohammad A.; Rahaju, Anny S. (Narra Sains Indonesia, 2024)
Contrast-induced acute kidney injury is a common complication marked by reduced kidney function within 48 hours of contrast administration. The aim of this study was to evaluate renal function, anatomy, and molecular changes at 24 hours, 48 hours, and 72 hours post-iodinated contrast media (ICM) administration. This true-experimental study used a post-test-only control group design. Rats underwent unilateral nephrectomy, followed by intravenous injection of ICM using iopromide 370 mg iodine/mL per rat at a dose of 231 mg iodine, and were then divided into four groups: control (C), rats terminated at 24 hours after iopromide administration (E24), rats terminated at 48 hours after iopromide administration (E48), and rats terminated at 72 hours (E72) after iopromide administration, with eight rats per group. Renal function (BUN and SCr levels) remained unchanged after 24, 48, and 72 hours of iopromide administration. Iopromide increased renal tubular damage, as shown by higher histopathological scores for loss of brush border and tubular necrosis, except for proteinaceous casts, where histopathological scores increase especially within the first 24 hours and decrease after 72 hours. Iopromide significantly altered iNOS expression in the glomerulus at 24 and 48 hours, and iNOS expression was decreased after 72 hours. iNOS expression in the intrarenal vascular and tubules was unaffected by iopromide administration. In conclusion, this study found no changes in renal function parameters, improvement in proteinaceous casts, and increased iNOS expression in the glomerulus, offering new insights into the effects of contrast on kidneys.